2008
DOI: 10.1080/10826080701203021
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Drug Expectancies as Anticipated Changes in Affect: Negative Reinforcement Is Not Sedation

Abstract: Goldman and Darkes (2004) argued that all three basic alcohol-expectancy factors can be assessed with a brief questionnaire (AEMax), related to the circumplex model of emotion. I argue that negative reinforcement, one of the three basic expectancy factors, is not assessed with the AEMax. Importantly, negative reinforcement is positively related to problem drinking while sedation (the AEMax-factor that comes closest) is not. In a new dataset (from 119 students, collected in 2002), I demonstrate that sedation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 56 publications
1
23
0
1
Order By: Relevance
“…Specifically, individuals seeking the sedative effects of alcohol may in fact drink more while on quetiapine in order to reach those desired effects. Research with heavy drinkers has found that sedative effects of alcohol may be protective against alcohol use and distinct from the negative reinforcing effects of alcohol (Ray et al 2009;Wiers 2008); however, there is the potential for the sedative effects of alcohol to serve as negative reinforcers, particularly in alcohol-dependent drinkers (Stritzke et al 1995). Of note, in the present study, the association between self-reports of sedation and self-reports of alcohol craving during the active alcohol administration was positive and nonsignificant (r=0.23 to 0.38), and a similar pattern was found for subjective intoxication (SHAS; r=0.27 to 0.49).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, individuals seeking the sedative effects of alcohol may in fact drink more while on quetiapine in order to reach those desired effects. Research with heavy drinkers has found that sedative effects of alcohol may be protective against alcohol use and distinct from the negative reinforcing effects of alcohol (Ray et al 2009;Wiers 2008); however, there is the potential for the sedative effects of alcohol to serve as negative reinforcers, particularly in alcohol-dependent drinkers (Stritzke et al 1995). Of note, in the present study, the association between self-reports of sedation and self-reports of alcohol craving during the active alcohol administration was positive and nonsignificant (r=0.23 to 0.38), and a similar pattern was found for subjective intoxication (SHAS; r=0.27 to 0.49).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, associations are bidirectional, while expectancies rely more on “if … then” relations (36). Although expectancies sometimes rely on a single association (e.g., drinking alcohol and fun), this is not always the case, as for instance in expectancies related to negative reinforcement (37). Whereas direct measures require conscious introspection, indirect measures tap into associations that influence behavior relatively automatically or unconsciously.…”
Section: Introductionmentioning
confidence: 99%
“…In line with previous research (e.g., , 2007a, 2007bWiers et al, 2002; see also Wiers, 2008), positive and negative explicit alcohol-related expectancies were measured with an expectancy questionnaire that asked participants to indicate on a 7-point Likert scale how much they agreed (1 completely disagree, 7 completely agree) with the statement, "After drinking alcohol, I feel . .…”
Section: Iat Effectsmentioning
confidence: 99%